'An Unrivalled Paradise': The Production of Difference in the Cuban Ministry of Tourism's Auténtica Cuba. (1st April 2019) - Bacsán, Gabriela
Abstract : Utilising an interdisciplinary methodology that draws from cultural studies and critical tourism studies, this article examines the production of difference at the intersection of hedonism and revolution in the Cuban Ministry of Tourism's international campaign, Auténtica Cuba. I analyse how the campaign's feature film, Auténtica Cuba, carefully crafts a narrative of authenticity in its construction of the island as 'an unrivalled paradise'. I pay close attention to how the production, commodification and marketing of Cuban difference for tourist consumption is contested and perpetuated, especially as difference is embodied by Afro-Cubans in the film. I conclude by considering whether the campaign provides what Stuart Hall terms, effective translation, in its aims to challenge the gendered, racialised and sexualised constructions of Cuba and Cubans as objects for tourist consumption. As tourism shapes and is shaped by neocolonial discourses of difference, this work is timely as – in light of the speculation about future transformations on the island – it considers the implications of the state's renewed framing of the expansion of tourism development as central to the work of the revolution.